Pengaruh Quick Ratio, Inventory Turnover dan Net Profit Margin Terhadap Pertumbuhan Laba (Studi Empiris Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bei Periode 2013-2018) - Yusri Yusri; Cut Delsie Hasrina; Vivin Windayati (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This research aims to determine the effect of quick ratio, inventory turnover and net profit margin on profit growth in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2018.Quick ratio offset by inventory turnover and net profit margin is expected to increase profit growth. The population in this study is a food and beverage subsector manufacturing company listed on the Indonesia Stock Exchange for the period 2013-2018. The selection of samples using purposive sampling techniques, the number of companies sampled in this study is as many as 13 companies. The data collection technique used in this study is a method of documenting studies by obtaining data in the form of annual reports of companies. The data analysis used is a resumed deskrifative analysis of classic assumption tests that include normality tests, heterogeneticity tests, multicholinerity tests and autocorcord tests. Hypothetical testing in this study used multiple regression analyst techniques. Based on the results of the study shows that: 1)quick ratio partially does not have a significant effect on profit growth with sig-t 0.152. 2) inventory turnover has no significant effect on profit growth with sig-t 0.643. 3) net profit margin partially affects profit growth with a sig-t value of 0.000. 4) quick ratio, inventory turnover and net profit margin simultaneously have a significant effect on profit growth with a sig-f value of 0.000.